Identifying ABO Blood Group and Rh Status Using Dried Saliva Samples - Ajit Pal Singh; Aishna Bhist (International Journal of Pathogens, 2024)
This article discusses the accuracy of dried saliva samples in establishing ABO and Rh blood types. Participants, likely screened for secretor status beforehand, submitted blood and saliva samples. Both samples were ABO blood typed (A, B, AB, or O) using standard methods such as gel card technology or hemagglutination assays. We used both saliva and blood to perform Rh typing. The findings revealed that saliva and blood typing for ABO groups corresponded nearly perfectly, highlighting the promise of saliva-based ABO identification, particularly for secretors. However, the correlation between the Rh type from saliva and the blood study was significantly weaker. This gap may be due to lower Rh antigen concentrations in saliva or limitations in existing testing techniques. Researchers have demonstrated that saliva serves as a feasible, non-invasive method for identifying the ABO blood group; however, additional research is required to enhance the precision of Rh typing from saliva. Future improvements in this area may include looking into non-invasive alternatives to Rh-factor assessment or developing more sensitive detection methods. A future study should focus on improving the sensitivity of saliva-based Rh detection methods, as well as investigating additional non-invasive methods such as tear or sweat analysis. Future blood group identification will become more comprehensive and reliable with the combination of this and advancements in prenatal Rh factor testing.
Keywords: Hemagglutination assays; Non-invasive blood typing; Rh typing accuracy; Saliva-based ABO identification; Secretor status